Incidence, determinants and clinical impact of left ventricular function recovery after surgical treatments for ischaemic cardiomyopathy. (29th March 2021) - Nakae, Masaro; Kainuma, Satoshi; Toda, Koichi; Miyagawa, Shigeru; Yoshikawa, Yasushi; Hata, Hiroki; Yoshioka, Daisuke; Kawamura, Takuji; Kawamura, Ai; Kashiyama, Noriyuki; Komukai, Sho; Kitamura, Tetsuhisa; et al.
Abstract:  : OBJECTIVES: This retrospective study aimed to clarify the incidence, determinants and clinical impact of left ventricular (LV) function non-recovery after coronary artery bypass grafting (CABG) in patients with ischaemic cardiomyopathy. METHODS: A total of 490 patients with ischaemic cardiomyopathy (LV ejection fraction ≤ 40%) undergoing CABG were analysed. Follow-up echocardiography was performed at 1 month, 1 year, and annually thereafter. LV function recovery was defined as ejection fraction (EF) ≥40% at least once during follow-up. LV function non-recovery was defined as EF <40% at any follow-up. The primary and secondary end points were changes in LV function and all-cause mortality, respectively. Clinical follow-up was completed in 461 patients (94.1%; mean follow-up: 64.5 ± 45.5 months). RESULTS: During follow-up, echocardiographic assessments were performed 1863 times (mean, 3.8 ± 2.4), and 193 patients (39.4%) exhibiting LV function non-recovery were identified. Overall survival was significantly higher in the recovery group (53.9%) than in the non-recovery group (31.4%) at 10 years ( P  < 0.001). Independent predictors of LV function non-recovery were preoperative LV end-systolic diameter [odds ratio (OR) 1.07, 95% confidence interval (CI) 1.04–1.10; P  < 0.001] and bilateral internal thoracic artery grafting (OR 0.61, 95% CI 0.39–0.95; P  = 0.028). In a multivariable Cox proportional hazards model, LV function non-recovery was significantly associated with all-cause mortality (hazard ratio 2.14, 95% CI 1.60–2.86; P  < 0.001). CONCLUSIONS: Almost 40% of patients with ischaemic cardiomyopathy undergoing CABG did not achieve LV function recovery and were associated with poor prognosis. To achieve LV function recovery, CABG with bilateral internal thoracic artery may be recommended before excessive LV remodelling occurs. Clinical trial registration number: Institutional review board of Osaka University Hospital, number 16105.